Problems in English-Chinese and Chinese-English legal translation: with a case study of mistranslations - Chan, Clara Ho-yan; Galdia, Marcus (Comparative Legilinguistics, 2023)
In this article, characteristic features of the Chinese legal language are approached from the perspective of legal translation from and into Chinese. The main focus is put upon the emergence of meaning in legal texts, which is reflected in the process of legal translation. Problems of meaning emergence in the Chinese law are regularly connected to legal transfers and legal implants borrowed from foreign languages such as English as well as other text forming devices. Translation is regularly inherent in such processes. As a result, legal translation influences processes in which legislation and the legislative language are shaped. Meanwhile, general problems of translation remain out of the scope of this study. Therefore, specific features of translation of legal texts from and into Chinese dominate the discussed issues. These specific issues include some little-explored ones such as translating traditional Chinese law and social attitudes to legal translation. Moreover, Chinese is the language of legislation and of court and administrative procedures in several jurisdictions as well as in numerous international organizations. Its legal status differs from jurisdiction to jurisdiction and displays its pluricentric character. Legal acts that are issued in these jurisdictions demonstrate therefore different levels of terminological formation and other legal-linguistically relevant varieties. It is the task of legal lexicography to register lexical varieties of legal Chinese in the relevant jurisdictions. Examples based on translations of legal texts in Mainland China, Hong Kong and Macau complement the main corpus of the article. The analysed texts show that legal translation and shaping legal language are closely interrelated creative activities.